Determination of Rheological Behavior of Some Molasses-Sesame Blends - Kamışlı, Fethi; Mohammed, Dlshad Abdalla (Fırat University, 2019)
The aim of this study is to determine the rheological properties of some molasses-tahin blends such as date syrup-tahin, mulberry molasses-tahin, grape molasses-tahin and carob syrup-tahin (sesame paste) blends at the different ratios (20-55 %) and different temperatures (25-60°C) by using a rotary viscometer to develop models appropriate to the experimental data. The variation of viscosity of those blends with the strain rates (2.5-30 s-1) showed that all considered ratios of the molasses-tahin blends were shear thinning fluids at the considered temperatures. The apparent viscosities of the blends as a function of shear strain were successfully described with the Power-law model. The model parameters such as the flow behavior index (n) and the consistency coefficient (K) of the considered blends were determined according to the experimental data. It was observed that apparent viscosities and consistency coefficients of blends increased with increasing molasses concentration and decreasing temperature. Activation energies (Ea) of the considered blends were determined. The relationship between concentration and consistency coefficient for each blend was described with both the exponential and power functions. A mathematical model was determined to describe the combined effects of temperature, concentrations of the molasses and shear strain on apparent viscosity with high consistency.
Keywords: Engineering; Mühendislik